2013
DOI: 10.1155/2013/162094
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Protoporphyrin Upregulates Heme Oxygenase-1 in PC-3 Cells via the Stress Response Pathway

Abstract: Zinc protoporphyrin IX (ZnPP), a naturally occurring molecule formed in iron deficiency or lead poisoning, is a potent competitive inhibitor of heme oxygenase-1 (HO-1). It also regulates expression of HO-1 at the transcriptional level. However, the effect of ZnPP on HO-1 expression is controversial. It was shown to induce HO-1 expression in some cells, but suppress it in others. The objective of this study is to investigate the effect of ZnPP on HO-1 expression in prostate cancer PC-3 cells. Incubation of PC-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…ZnPP by itself did not induce HMOX1 expression (Figure 8B ). However, when combined with ATO, ZnPP had a dual effect: 1) it potentiated the increase on HMOX1 expression induced by ATO, in agreement with the reported role of ZnPP as an inducer of HMOX1 and an inhibitor of its activity [ 33 , 34 ]; 2) it affected HMOX1 mobility in gels, suggesting that besides inhibiting HMOX1 activity, ZnPP binding induced a conformational change in HMOX1, further confirming the activity of this compound (Figure 8B ).…”
Section: Resultssupporting
confidence: 86%
“…ZnPP by itself did not induce HMOX1 expression (Figure 8B ). However, when combined with ATO, ZnPP had a dual effect: 1) it potentiated the increase on HMOX1 expression induced by ATO, in agreement with the reported role of ZnPP as an inducer of HMOX1 and an inhibitor of its activity [ 33 , 34 ]; 2) it affected HMOX1 mobility in gels, suggesting that besides inhibiting HMOX1 activity, ZnPP binding induced a conformational change in HMOX1, further confirming the activity of this compound (Figure 8B ).…”
Section: Resultssupporting
confidence: 86%
“…MPs not only inhibit the activity of both isoenzymes of HO [ 86 ] but because of the similarity of structure to heme, most of them also affect other heme-dependent enzymes like nitric oxide synthases (NOS), soluble guanylyl cyclase (sGC) or cytochromes P450 (CYPs) [ 87 , 88 ]. Paradoxically, they also induce HO-1 on mRNA and protein level [ 9 , 89 , 90 , 91 ]. These wide-ranging actions cause potential concerns in the interpretation of effects ascribed to MPs.…”
Section: Pharmacological Inhibition Of Ho-1 Activitymentioning
confidence: 99%
“…Recently, the heme oxygenase/carbon monoxide (HO/CO) system has attracted a great deal of attention. HO-1, which has constitutive and inducible isoforms ( 6 , 7 ), catalyzes the rate-limiting step in the oxidative degradation of heme to biliverdin ( 8 ), releasing equimolar quantities of CO and iron ( 9 ). Previous studies have shown that hepatic HO-1 was overexpressed in cirrhotic rats ( 10 ) and contributed to portal hypertension ( 11 ).…”
Section: Introductionmentioning
confidence: 99%